The nature of the early Ottoman state - Lowry, Heath W., 1942- (Albany : State University of New York Press, 2003)
Drawing on surviving documents from the fourteenth and fifteenth centuries, The Nature of the Early Ottoman State provides a revisionist approach to the study of the formative years of the Ottoman Empire. Challenging the predominant view that a desire to spread Islam accounted for Ottoman success during the fourteenth-century advance into Southeastern Europe, Lowry argues that the primary motivation was a desire for booty and slaves. The early Ottomans were a plundering confederacy, open to anyone (Muslim or Christian) who could meaningfully contribute to this goal. It was this lack of a strict religious orthodoxy, and a willingness to preserve local customs and practices, that allowed the Ottomans to gain and maintain support. Later accounts were written to buttress what had become the self-image of the dynasty following its incorporation of the heartland of the Islamic world in the sixteenth century.
8. THE NATURE OF THE EARLY OTTOMAN STATE -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Z -- SUNY Series in the Social and Economic History of the Middle East.
Includes bibliographical references (pages 177-189) and index.
Print version record.
English.
JSTOR
Keywords: Turkey -- Civilization; Turkey -- Social conditions; Turkey -- History; Turquie -- Conditions sociales; Turquie -- Histoire; HISTORY -- General; Civilization; Social conditions; Turkey; History